Review of disease transmission risks from prawn products exported for human consumption - T. W. Flegel (2018)
Recent publications have proposed that transmission of exotic viral pathogens to cultured and native shrimp stocks may be possible via frozen prawn products prepared and packaged for human consumption. To properly assess the probability of such disease transmission, epidemiological analysis would be required. This analysis might necessitate new investigations to quantify the risks associated with intended and non-intended product use. It would also require a review and analysis of published literature on transmission of shrimp pathogens from frozen shrimp products, of existing prawn fishery and aquaculture statistics, and of published literature on disease epidemics in wild and cultivated shrimp. This review revealed no published reports in the peer-reviewed, scientific literature of shrimp disease outbreaks in wild or cultivated shrimp that originated from shrimp packaged and processed for retail sale. Similar conclusions have been reached for chilled and frozen eviscerated fish and mollusk products prepared and packaged for human consumption. Reports were found describing successful laboratory transmission of shrimp viruses from packaged fresh frozen shrimp under specific laboratory conditions, but these did not include epidemiological analyses to determine the probable risk of transmission to wild or cultivated shrimp stocks under conditions of product marketing and use. Other more likely routes of possible shrimp viral transmission are also reviewed and risk reduction measures are recommended. © 2009 Elsevier B.V. All rights reserved.